The Central American Coffee Crisis : Effects and Strategies Forward - Castro, Felipe; Montes, Eduardo; Raine, Martin (World Bank, Washington, DC, 2012)
This brief includes the following headlines: structural changes in the global coffee market: the impact on Central America; economic effects of the coffee crisis; yields and production costs; effects of the crisis on employment in the coffee sector; responses to the crisis; strategies for promoting competitiveness and diversification; an analysis of sustainable coffee production in Central America; environmental considerations; recommendations; and about the authors.